Primary vitamin D target genes allow a categorization of possible benefits of vitamin D₃ supplementation. - Carsten Carlberg (Public Library of Science (PLoS), 2013)
Vitamin D deficiency has been associated with an increased risk of developing a number of diseases. Here we investigated samples from 71 pre-diabetic individuals of the VitDmet study, a 5-month high dose vitamin D3 intervention trial during Finnish winter, for their changes in serum 25-hydroxyvitamin D3 (25(OH)D3) concentrations and the expression of primary vitamin D target genes in peripheral blood mononuclear cells and adipose tissue. A negative correlation between serum concentrations of parathyroid hormone and 25(OH)D3 suggested an overall normal physiological vitamin D response among the participants. The genes CD14 and thrombomodulin (THBD) are up-regulated primary vitamin D targets and showed to be suitable gene expression markers for vitamin D signaling in both primary tissues. However, in a ranking of the samples concerning their expected response to vitamin D only the top half showed a positive correlation between the changes of CD14 or THBD mRNA and serum 25(OH)D3 concentrations. Interestingly, this categorization allows unmasking a negative correlation between changes in serum concentrations of 25(OH)D3 and the inflammation marker interleukin 6. We propose the genes CD14 and THBD as transcriptomic biomarkers, from which the effects of a vitamin D3 supplementation can be evaluated. These biomarkers allow the classification of subjects into those, who might benefit from a vitamin D3 supplementation, and others who do not.